Profile of female swimmers competing in the 50 m events at the 2021 LEN European Championships - Oliveira, J. P.; Marinho, D. A.; Barbosa, T. M.; Sampaio, T.; Morais, J. E. (International Journal of Performance Analysis in Sport, 2023)
This study aimed to understand whether there are significant differences in stroke kinematics between tiers in female swimmers competing in the four 50 m events of the 2021 European Championships and to understand the speed-time relationship in the four race events per tier. Participants were all female swimmers (backstroke: 78 swimmers; breaststroke: 75 swimmers; butterfly: 74 swimmers; freestyle: 87 swimmers) who participated in the 50 m events at the 2021 LEN European Championships held in Budapest (i.e. heats, semi-finals, and final). For each swimming stroke, swimmers were divided into three tiers (best-performing swimmers, intermedium-performing swimmers, and poorest-performing swimmers). Swimming speed revealed a significant tier effect (p < 0.05) in all race sections for all swimming strokes. The other stroke kinematic variables revealed divergent findings, but the stroke frequency presented an overall tier effect (p < 0.05) across all four swimming strokes. Curve fitting for all swimming strokes and tiers revealed a cubic relationship. Thus, it should be considered that female swimmers who compete in 50 m events in major competitions adopt an all-out strategy. The present data provide coaches with insightful information about the main trend in 50 m sprint events, specifically in each section of the race.